Spanish Validation of the Shorter Version of the Workplace Incivility Scale: An Employment Status Invariant Measure - Di Marco, Donatella; Martínez-Corts, Inés; Arenas, Alicia; Gamero, Nuria (Frontiers in Psychology, 2018)
Workplace Incivility (WI) occurs worldwide and has negative consequences on individuals and organizations. Valid and comprehensive instruments have been used, specifically in English speaking countries, to measure such adverse process at work, but it is not available a validated instrument for research carried out in Spanish speaking countries. In this study we aim to test the psychometric properties of the Matthews and Ritter’s four-item Workplace Incivility Scale (2016) with Spanish workers (N= 407) from different sectors. Participants’ mean age was 38.73 (SD= 10.45) years old and the percentage of female employees was 59.2%. Confirmatory factor analysis using AMOS 19.0 was carried out, presenting a good fit. The internal consistency, convergent and concurrent validity of the scale were examined. Results show good scale reliability and expected high correlations with social undermining. Moreover, the scale related to propensity to leave a job, job satisfaction, and psychological well-being in the expected way. After configural invariance across groups was established, testing for metric invariance and scalar invariance was performed. Considering Δχ² and ΔCFI tests for two nested models, the 4-item scale was invariant when the employment status is considered (permanent vs temporal, full-time vs part-time and supervisor vs non supervisors). Overall, our findings showed good psychometric properties of the shorter version of the Workplace Incivility Scale in Spain. Theoretical and practical implications of this study are discussed.